To solve the equation \( 18 - 3(1d + 5) = 3d - 12 \), we'll start by expanding and simplifying the left side:
-
Distribute \(-3\) into the parentheses: \[ 18 - 3(1d) - 3(5) = 18 - 3d - 15 \]
-
Combine like terms on the left side: \[ 18 - 15 - 3d = 3 - 3d \]
So the equation now reads: \[ 3 - 3d = 3d - 12 \]
Next, we can rearrange the equation to isolate \(d\):
-
Add \(3d\) to both sides: \[ 3 = 3d + 3d - 12 \] Which simplifies to: \[ 3 = 6d - 12 \]
-
Add \(12\) to both sides: \[ 3 + 12 = 6d \] Simplifying gives: \[ 15 = 6d \]
-
Divide both sides by \(6\): \[ d = \frac{15}{6} = \frac{5}{2} = 2.5 \]
So the final answer is: \[ d = 2.5 \]